2017
DOI: 10.1016/j.radcr.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Arterial spin labeling perfusion imaging demonstrates cerebral hyperperfusion in anti-NMDAR encephalitis

Abstract: Anti-N-methyl-d-aspartate receptor encephalitis is an increasingly recognized autoimmune disorder that results in substantial morbidity, prolonged hospital stays, and even death. The diagnosis is often delayed or unrecognized entirely as a result of absent or only subtle initial magnetic resonance imaging findings and a nonspecific clinical syndrome. The discovery of early imaging findings in this disease may help clinicians to more aggressively treat this autoimmune encephalitis and to potentially lessen morb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 8 publications
(16 reference statements)
1
23
0
Order By: Relevance
“…Second, the presence of hyperperfusion on CT perfusion exam of the brain with corresponding decreased diffusivity and T2-FLAIR hyperintensity in the cortex of the left parietooccipital lobe was observed. A very recent case report (in December 2017) has also found increased cerebral blood flow on arterial spin labelling in in anti-NMDA receptor encephalitis [10]. This case illustrates similar findings in anti-GAD encephalitis with CT perfusion.…”
Section: Discussionsupporting
confidence: 76%
“…Second, the presence of hyperperfusion on CT perfusion exam of the brain with corresponding decreased diffusivity and T2-FLAIR hyperintensity in the cortex of the left parietooccipital lobe was observed. A very recent case report (in December 2017) has also found increased cerebral blood flow on arterial spin labelling in in anti-NMDA receptor encephalitis [10]. This case illustrates similar findings in anti-GAD encephalitis with CT perfusion.…”
Section: Discussionsupporting
confidence: 76%
“…Although 33%–55% patients with anti‐NMDAR encephalitis show brain lesions (e.g., medial temporal, frontal, and parietal cortex), normal brain images are observed in the majority of patients with routine clinical MRI sequences 4 . In contrast, advanced multimodal MRI techniques can successfully detect brain alterations in anti‐NMDAR encephalitis, such as morphological atrophy, 6 disrupted white‐matter microstructure 7 and altered cerebral blood flow 8 . Beyond the focal alterations, recent studies have demonstrated that anti‐NMDAR encephalitis is associated with impaired interregional connectivity not only in single neural circuit 7 but spanning multiple distributed brain systems, 9 implying that anti‐NMDAR encephalitis is a global network dysfunctional disease.…”
Section: Introductionmentioning
confidence: 99%
“…Given the metabolism-perfusion coupling, we investigated ASL in the acute phase. Very few studies exist on ASL in NMDAR encephalitis [5]. To our best knowledge, focal hypoperfusion on ASL, corresponding to occipito-parietal hypometabolism on 18 F-FDG-PET, has never been reported.…”
Section: Discussionmentioning
confidence: 96%